2013
DOI: 10.1063/1.4801096
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic force measurements under precisely controlled conditions: Correlation of slip parameters with the mean free path

Abstract: A customized atomic force microscope has been utilized in dynamic mode to measure hydrodynamic forces between a sphere and a flat plate, both coated with gold. In order to study the influence of the mean free path on slippage without systematic errors due to varying surface properties, all data have been acquired at precisely the same spot on the plate. Local accommodation coefficients and slip lengths have been extracted from experimental data for He, Ne, Ar, Kr, as well as N2, CO2, and C2H6, at Knudsen numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…What is perhaps surprising is that most He atoms appear to reflect specularly from the diamond surface. In fact, any roughness on the surface will tend to reduce the fraction of particles that are reflecting specularly, and our surfaces have rms roughness ≲10 nm, as noted above. In order to modify eq to accurately incorporate the effect of roughness in K , the spatial distribution (dominant wavelengths) of roughness ought to be taken into account in addition to its rms value.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…What is perhaps surprising is that most He atoms appear to reflect specularly from the diamond surface. In fact, any roughness on the surface will tend to reduce the fraction of particles that are reflecting specularly, and our surfaces have rms roughness ≲10 nm, as noted above. In order to modify eq to accurately incorporate the effect of roughness in K , the spatial distribution (dominant wavelengths) of roughness ought to be taken into account in addition to its rms value.…”
mentioning
confidence: 74%
“…What is perhaps surprising is that most He particles appear to reflect specularly from the diamond surface. In fact, any roughness on the surface will tend to reduce the fraction of particles that are reflecting specularly [39][40][41], and our surfaces have r.m.s. roughness < ∼ 10 nm, as noted above.…”
Section: B Gas: Surface Accommodationmentioning
confidence: 98%
“…This is the dimension of nanomicrofluidics and nanomicroelectromechanical systems (NEMS and MEMS). In fact, previous measurements show that the assumption of slip flow remains reasonable even for L ∼ 70 nm at 1 atm ( Kn < 1), which broadens the applicability of the partial slip model. For macroscopic systems ( L ∼ 1 m), the applicable pressure for the slip flow regime is 10 –4 –10 –6 atm for N 2 .…”
Section: Introductionmentioning
confidence: 82%
“…Asproulis and Drikakis [22] suggested that the amount of slip versus wall stiffness can be modeled through a fifth-order polynomial function. Experiments on slip have shown that larger slips lengths occur with smaller surface roughness [23] and hydrophobic walls [24]. Niavarani and Priezjev [25], among others, pointed out that in the presence of periodic surface roughness, the magnitude of the effective slip length is significantly reduced.…”
Section: List Of Symbols C Vmentioning
confidence: 98%